Differences in the phenotypes and transcriptomic signatures of chimeric antigen receptor T lymphocytes manufactured via electroporation or lentiviral transfection - Niu, Anna; Zou, Jintao; Hu, Xuan; Zhang, Zhang; Su, Lingyu; Wang, Jing; Lu, Xing; Zhang, Wei; Chen, Wei; Zhang, Xiaopeng (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR)-T cell therapy is an innovative treatment for CD19-expressing lymphomas. CAR-T cells are primarily manufactured via lentivirus transfection or transposon electroporation. While anti-tumor efficacy comparisons between the two methods have been conducted, there is a current dearth of studies investigating the phenotype and transcriptome alterations induced in T cells by the two distinct manufacturing methods. Here, we established CAR-T signatures using fluorescent imaging, flow cytometry, and RNA-sequencing. A small fraction of CAR-T cells that were produced using the PiggyBac transposon (PB CAR-T cells) exhibited much higher expression of CAR than those produced using a lentivirus (Lenti CAR-T cells). PB and Lenti CAR-T cells contained more cytotoxic T cell subsets than control T cells, and Lenti CAR-T cells presented a more pronounced memory phenotype. RNA-sequencing further revealed vast disparities between the two CAR-T cell groups, with PB CAR-T cells exhibiting greater upregulation of cytokines, chemokines, and their receptors. Intriguingly, PB CAR-T cells singularly expressed IL-9 and fewer cytokine release syndrome-associated cytokines when activated by target cells. In addition, PB CAR-T cells exerted faster in vitro cytotoxicity against CD19-expressing K562 cells but similar in vivo anti-tumor efficacy with Lenti CAR-T. Taken together, these data provide insights into the phenotypic alterations induced by lentiviral transfection or transposon electroporation and will attract more attention to the clinical influence of different manufacturing procedures.